PROFILING STUDENTS’ SCIENTIFIC LITERACY SKILLS: A STUDY IN MADURA SECONDAY HIGH SCHOOL - Erlina Wardani; Mochammad Yasir; Mochammad Ahied (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
This study aims to describe the science literacy profile of students at SMPN 1 Tanjung Bumi. The research employed a descriptive method with a quantitative approach, allowing the collected data to be processed statistically to objectively illustrate the students' level of science literacy. The subjects of this study consisted of 35 students from class VIII A who were given six science literacy test items with a duration of one lesson hour. The data were analyzed using descriptive statistics to determine the categories of science literacy proficiency. The results show that most students have a level of science literacy that needs improvement, with 51% categorized as very low, 46% as low, and only 3% as adequate, while none of the students fell into the good or very good categories. Factors contributing to the low science literacy include misconceptions of scientific concepts, poor reading ability, lack of interest in science, and unfamiliarity with long-text and contextual problem types. Based on these findings, strategies are needed to enhance science literacy through the development of innovative learning materials, improvement of reading interest, and habituation to analytical and context-based problem-solving tasks. These findings indicate the need for learning interventions grounded in local context to improve students' science literacy skills. Keywords: scientific literacy, students, junior high school